Experience Economy as an Irrational Philosophy in Tourist and Hotel Services in Transforming the Socio-Economic Systems - Gazgireeva, Larisa; Churilina, Irina; Semenova, Liudmila (Anais Brasileiros de Estudos Turísticos, 2022)
The aim of this concepotual paper is to develop recommendations for the implementation of a strategy for marketing impressions in tourism and hospitality enterprises, thereby emphasizing the importance of the role of the impressions economy in the provision of tourist and hotel services in the context of the transformation of socio-economic systems. The strengthening of the concept of impressions economy is a certain reaction to the changing conditions in the service economy.The article analyzes a new type of relationship between the brand and the consumer - marketing of impressions, as well as the conditions that contribute to the successful functioning of tourism and hospitality enterprises, thereby emphasizing the fact that there is a mass process in the consumption of hotel and tourist services and the formation of certain value positions. Analyzing the problem of the role of impressions marketing in the provision of tourist services and hotel products in the context of the transformation of socio-economic systems, it was revealed that the concept of impressions economics at the beginning of the 21st century strengthens its position, which is manifested in the limitless nature of postmodern hedonism among modern consumers of the service sector.